Peran Public Relations Pada Isu PLTU Suralaya - Puspaningtyas, Raden Roro Nadya; Lisnawati, Tamara; Sulistia, Imelda; Patrianti, Tria (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2024)
Air pollution cases are increasing in the Banten region allegedly due to air pollution by PT PLN (PLTU) which comes from the combustion process of one of its plants, thus emitting emissions or remnants of processing results from its chimney. The cause of air pollution is caused by the combustion of one of the plants but because of vehicle gas. So that these reasons can affect the image of the PLTU making PLTU Public Relations carry out various strategies in communicating the issue. The purpose of this study is to see how PR steps to build public trust in PLN (PLTU). This research uses qualitative methods with media monitoring from the mass media related to reporting on issues about air pollution caused by the Suralaya PLTU from February 23, 2021 - September 2023. This research states that the role of Public Relations in restoring the company's image in cases of air pollution caused by PLTU is to conduct media monitoring, media visits, make press releases, create programs in collaboration with stakeholders, help the government to reduce air pollution by spraying water at the top of PLN's head office tower, develop Corporate Social Responsibility (CSR) programs. As well as developing the